Spectrophotometric Determination of Raltgravir Potassium and Galantamine Hydrobromide Pharmaceuticals using Folin-Ciocalteu reagent and Iron (II) - Orthophenanthraline as Chromogenic agents - S. Hemambika; K. Raghu Babu; N. Annapurna (International Journal of Research in Chemistry and Environment (IJRCE), 2017)
Two simple, sensitive and selective methods are proposed for the determination of Raltgravir potassium(RAL) and Galantamine Hydrobromide(GLT) in pure drug and tablets. The first method is based on the reduction of Folin-Ciocalteu reagent (F-C) by RAL and GLT in Sodium carbonate to form a blue coloured complex ,which was measured at 810 nm and 800nm resp. (Molybdenum –Tungsten blue method ).In the second method (Prussian blue method),Iron (III) was reduced to Iron(II) by RAL and GLT in HCl medium, in which Iron (II) is complexed with Ferricyanide and the resulting Prussian blue was measured at 510nm ,630nm respectively. The absorbance measured in each case was related to the RAL and GLT concentrations. The experimental conditions were carefully studied and optimised. Beer’s law was obeyed in concentration ranges 0.1-0.5 µg/ml(RAL and GLT for method I) and 0.4-2.4µg/ml(RAL and GLT for method (II) corresponding molar absorptivity values 0.458×104 (1 mole cm-1) RAL and 2.75×105 (1 mole cm-1) for method I, 6.65×104 mole cm-1 1.166×105 mole cm-1 (RAL and GLT for method II. The LOD is 1.37(µg ml‑1) and 1.35(µg ml‑1) for method I, 7.95 µg ml‑1 and 2.716 µg ml‑1(RAL and GLT for method II.